Unraveling the Differential Functions and Regulation of Striatal Neuron Sub-Populations in Motor Control, Reward, and Motivational Processes - Ena, Sabrina; De Kerchove D'ExaErde, Alban; Schiffmann, Serge N. (Frontiers in Behavioral Neuroscience, 2011)
The striatum, the major input structure of the basal ganglia, is critically involved in motor control and learning of habits and skills, and is also involved in motivational and reward processes. The dorsal striatum, caudate-putamen, is primarily implicated in motor functions whereas the ventral striatum, the nucleus accumbens, is essential for motivation and drug reinforcement. Severe basal ganglia dysfunction occurs in movement disorders as Parkinson’s and Huntington’s disease, and in psychiatric disorders such as schizophrenia and drug addiction. The striatum is essentially composed of GABAergic medium-sized spiny neurons (MSNs) that are output neurons giving rise to the so-called direct and indirect pathways and are targets of the cerebral cortex and mesencephalic dopaminergic neurons. Although the involvement of striatal sub-areas in motor control and motivation has been thoroughly characterized, major issues remained concerning the specific and respective functions of the two MSNs sub-populations, D2R-striatopallidal (dopamine D2 receptor-positive) and D1R-striatonigral (dopamine D1 receptor-positive) neurons, as well as their specific regulation. Here, we review recent advances that gave new insight in the understanding of the differential roles of striatopallidal and striatonigral neurons in the basal ganglia circuit. We discuss innovative techniques developed in the last decade which allowed a much precise evaluation of molecular pathways implicated in motivational processes and functional roles of striatopallidal and striatonigral neurons in motor control and in the establishment of reward-associated behaviour.